1997
DOI: 10.1007/bf01628510
|View full text |Cite
|
Sign up to set email alerts
|

Double superior gemellus together with double piriformis and high division of the sciatic nerve

Abstract: We report a case with double superior gemellus and double piriformis mm. associated with the sciatic n. dividing high and passing between the two piriformis mm. in the same lower extremity. This abnormality has not previously been described in the literature. As many musculoskeletal structures may be involved in sciatica, the supernumerary superior gemelli and piriformis mm. may exert pressure on the sciatic n. and this should be taken into account by clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…We are led to believe that the variant muscle observed here represents a portion of piriformis that has developed erroneously from the superior portion of the muscle's embryological anlage, as evidenced by the loss the superior aspect of the normal piriformis muscle mass [2]. A duplicated superior gemellus was also noted on the left side similar to that described by Arifoglu et al [3].…”
Section: Case Studysupporting
confidence: 68%
“…We are led to believe that the variant muscle observed here represents a portion of piriformis that has developed erroneously from the superior portion of the muscle's embryological anlage, as evidenced by the loss the superior aspect of the normal piriformis muscle mass [2]. A duplicated superior gemellus was also noted on the left side similar to that described by Arifoglu et al [3].…”
Section: Case Studysupporting
confidence: 68%
“…Another case study of a male cadaver (63 years) showed a variation in the piriformis muscle, which presented as two bellies. Only the inferior belly (pictured as the smaller of the two bellies) originated from the STL by “a single digitation” (Arifoglu et al ) implying a small muscular interaction with the ligament. In a review paper, Smoll () report an attachment between piriformis and the STL, but provide no data, nor reference from which this information is derived.…”
Section: Resultsmentioning
confidence: 99%
“…Bent et al showed that if neurolymphomatosis is suspected, a nerve biopsy must be considered. They also emphasized that usually the sural nerve biopsy is necessary in order to demonstrate tumor cells (12).…”
Section: Discussionmentioning
confidence: 99%